2021
DOI: 10.1080/10413200.2021.2015480
|View full text |Cite
|
Sign up to set email alerts
|

Applied psychology of sport injury: Getting to—and moving across—The Valley of death

Abstract: Areas of science in which policy and practice lag behind research evidence are known as "valleys of death" (Reis et al., 2008). It can be argued that sport injury psychology has not yet reached, let alone crossed, its own valley of death. In this paper, we consider what developments in the evidentiary base are required to reach and cross the valley of death to advance the application of psychology to sport injury prevention and rehabilitation over the next 10 years. To that end, we reflect on the current resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 87 publications
(108 reference statements)
0
7
0
Order By: Relevance
“…High motivation levels were noted among the participants, with earlier research identifying both intrinsic and extrinsic motivators as drivers of rehabilitation 22 . Resilience and goal‐directed behavior has been shown to enhance satisfaction with the progress, 23,24 whilst goal setting has also been shown to contribute to rehabilitation adherence 25 . There was evidence of the participants adhering positively to their rehabilitation programs.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…High motivation levels were noted among the participants, with earlier research identifying both intrinsic and extrinsic motivators as drivers of rehabilitation 22 . Resilience and goal‐directed behavior has been shown to enhance satisfaction with the progress, 23,24 whilst goal setting has also been shown to contribute to rehabilitation adherence 25 . There was evidence of the participants adhering positively to their rehabilitation programs.…”
Section: Discussionmentioning
confidence: 77%
“…22 Resilience and goal-directed behavior has been shown to enhance satisfaction with the progress, 23,24 whilst goal setting has also been shown to contribute to rehabilitation adherence. 25 There was evidence of the participants adhering positively to their rehabilitation programs. Previous research showed that such adherence positively affected successful RTS, however, withdrawal and isolation hampered adherence.…”
Section: Repair (Week 2-6 Post-surgery)mentioning
confidence: 99%
“…Consequently, even more relevant contributions are expected in the upcoming years. Injury prevention and rehabilitation is one of the application domains of sport psychology where there is a considerable gap between research evidence and practice [ 92 ]. What is needed are well-controlled studies demonstrating the benefits of sport psychological interventions for both athletes and coaches alike.…”
Section: Diagnosis Of Stressmentioning
confidence: 99%
“…[6][7][8] There are, however, few structured interventions aiming to improve psychological aspects of rehabilitation, 9 though the literature has called for a more thorough exploration of potential strategies. 10 We have proposed and are currently evaluating the Motor Imagery to Facilitate…”
Section: Introductionmentioning
confidence: 99%
“…Higher motivation, optimism, self-confidence and lower fear of reinjury have been suggested to increase the likelihood of successful rehabilitation outcomes, such as return to activity 6–8. There are, however, few structured interventions aiming to improve psychological aspects of rehabilitation,9 though the literature has called for a more thorough exploration of potential strategies 10…”
Section: Introductionmentioning
confidence: 99%